Penerapan Pewarnaan Graf Terhadap Penyusunan Jadwal Seminar Proposal Skripsi di Prodi Pendidikan Matematika UIN Raden Intan Lampung - Novian Riskiana Dewi (Universitas PGRI Adi Buana Surabaya, 2020)
Mathematics Education of UIN Raden Intan Lampung has a problem in the process of preparing the thesis proposal seminar schedule, because there are many students who conduct seminars in the adjacent period. During this time the preparation of the proposal seminar schedule is done manually, not infrequently many schedule lecturers and examiners are clashing with other student proposal seminar schedules. To overcome these problems, a thesis proposal seminar schedule was arranged by applying the concept of point coloring to graphs using the Welch Powell Algorithm. The points on the graph are represented as students who will conduct a thesis proposal seminar, while the side that connects the two points states that these two points have one and / or two supervisors. The research method used is the study method of literature study. The results of this study indicate that graph coloring using Welch Powell algorithm can be applied to arrange seminar schedule for students' thesis proposal for Mathematics Education, Faculty of Tarbiyah and Teacher Training. UIN Raden Intan Lampung.